2023
DOI: 10.1039/d2rp00165a
|View full text |Cite
|
Sign up to set email alerts
|

Social support and continuing motivation in chemistry: the mediating roles of interest in chemistry and chemistry self-efficacy

Abstract: Continuing motivation in science can promote science literacy, identity, and lifelong learning, which has received considerable attention. As a crucial part of the science discipline, the study on continuing motivation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 121 publications
0
7
0
1
Order By: Relevance
“…La motivación y diversión que se observó en todos los participantes fue muy evidente. Al respecto, en ocasiones este tipo de variables subjetivas son menospreciadas ante variables cognitivas como el conocimiento o las habilidades (Huangfu et al, 2023). Sin embargo, existe evidencia entre la relación existente sobre la experiencia significativa y agradable con el desempeño académico.…”
Section: Resultados Y Discusiónunclassified
“…La motivación y diversión que se observó en todos los participantes fue muy evidente. Al respecto, en ocasiones este tipo de variables subjetivas son menospreciadas ante variables cognitivas como el conocimiento o las habilidades (Huangfu et al, 2023). Sin embargo, existe evidencia entre la relación existente sobre la experiencia significativa y agradable con el desempeño académico.…”
Section: Resultados Y Discusiónunclassified
“…In the same study, perceived support from friends for science was related to self-concept and utility value, but not intrinsic value. In another study, Chinese high school students' self-efficacy and interest in chemistry was found to be positively predicted by perceived support from both teachers and peers (Huangfu et al, 2023). Finally, Leaper et al (2012) found that peer support for science was positively related to girls' science motivation (a combined measure of self-concept, intrinsic value, and utility value) in an ethnically diverse sample from North America.…”
Section: Social Support Self-efficacy and Task Valuesmentioning
confidence: 93%
“…Taken together, these studies suggest that teacher and peer support are important for science expectancies and values, but also highlight the relatively limited body of literature which has focused on the role of classroom-based social support in adolescents' science motivation. For example, while teacher support appears to be positively related to self-concept and intrinsic value (Hsieh et al, 2019;Huangfu et al, 2023) only Hsieh et al (2019) have examined the relationship between teacher support and utility value specifically. There are also conflicting findings regarding the role of peer support, as peer support was not related to intrinsic value of science in one study (Hsieh et al, 2019) but was positively related to interest in chemistry in another (Huangfu et al, 2023).…”
Section: Social Support Self-efficacy and Task Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that choosing a STEM career is influenced by personal factors (e.g., interest, self-efficacy, perception of the subject) and environmental-social factors (e.g., family, teachers, peers, social background) (Chakraverty and Tai, 2013;Venville et al, 2013;Lo ´pez et al, 2023). Many studies have been conducted on elementary and high school students' choice of STEM learning and career (Guo et al, 2022;Huangfu et al, 2022;Ofek-Geva et al, 2023), with fewer focusing on university education and the factors that influence undergraduate students to choose to major specifically in chemistry. (Ogunde et al, 2017;Avargil et al, 2020;Archer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%